A internet como fonte de informação para inteligência empresarial: um estudo de caso em indústrias de micro, pequeno e médio portes - Joubert Roberto Ferreira Fidelis (2001)
The Business Intelligence (BI) is a fundamental function to the development of the organizations because it permits the gathering of external information for decision-making and the development of strategic planning. This study discusses the practices adopted by managers of small and medium size enterprises in the metal mechanical industry for monitoring and gathering the information needed in their activities. The companies are situated in Vale do Aço region in the state of Minas Gerais, Brazil. Beginning from the identification of information needs this study include topics such as the implementation of BI function and their information sources. It also discusses the use of Internet and its resources while information source for BI.